Studi Literatur Faktor-Faktor Yang Berhubungan Dengan Kepatuhan Minum Obat Anti Tuberculosis (OAT) Pada Pasien TBC - Elisabet Matulessy; Chendy Sofianty Pelatta; Ravenska Pattiwael (MOLUCCAS HEALTH JOURNAL, 2021)
Tuberculosis is a chronic infectious disease caused by the bacterium Mycobacterium tuberculosis. This bacterium is rod-shaped and is acid-fast, so it is often known as Acid-Resistant Basil (BTA). The source of transmission is smear positive TBC patients through the sputum sprinkles they excrete. The purpose of this study was to determine the description of knowledge, motivation for healing and family support with adherence to taking Anti Tuberculosis Drugs (OAT) in TBC patients in 2021. The design of this study was descriptive using the Systematic Review method. The method used is to examine the results of other parties' research. Sampling in this study was carried out by a screening process with a sample of 16 research journals. The results of this study are in accordance with 16 research journals showing that there is a significant relationship between knowledge, healing motivation and family support with adherence to taking Anti Tuberculosis Drugs (OAT) in TBC patients. Conclusion: there is a significant relationship between knowledge, healing motivation and family support with adherence to taking Anti Tuberculosis Drugs (OAT). Suggestions for tuberculosis sufferers to comply with treatment for 6 months or according to the time recommended by health workers and for families to be supervisors of taking medication for patients, play an active role in providing support and motivation for patients in the treatment stage.Keywords: TBC, OAT adherence, Knowledge, Healing Motivation, Family Support